2021
DOI: 10.1016/j.diabet.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Fasting plasma glucose variability in midlife and risk of Parkinson's disease: A nationwide population-based study

Abstract: Background -Athough an association exists between type 2 diabetes and Parkinson's disease (PD), the implications of glycemic variability on PD are unknown. We assessed the future risk of incident PD according to visit-to-visit fasting plasma glucose (FPG) variability; this was calculated using standard deviation (FPG-SD), coefficient variance (FPG-CV), and variability independent of the mean (FPG-VIM).Methods -Using the Korean National Health Insurance Service-Health Screening Cohort, we followed 131,625 Korea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Similarly, the ratio of men and women did not account for differential study effects ( P = 0.165). We then considered the cohort studies separately depending on when enrolment to the study occurred relative to the onset of the exposure (T2DM) under the assumption that the effect of survival bias in those with exposure before enrolment (ie, unobserved) would be greatest 35 . In one cohort study, the onset of T2DM was before the period of observation (OR 0.88, 95% CI 0.62–1.25), two of the cohort studies enrolled incident cases of T2DM (pooled OR 1.27, 95% CI 1.15–1.40), and the remaining four cohort studies used a combination of methods to determine the T2DM (pooled OR 1.38, 95% CI 1.24–1.55; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the ratio of men and women did not account for differential study effects ( P = 0.165). We then considered the cohort studies separately depending on when enrolment to the study occurred relative to the onset of the exposure (T2DM) under the assumption that the effect of survival bias in those with exposure before enrolment (ie, unobserved) would be greatest 35 . In one cohort study, the onset of T2DM was before the period of observation (OR 0.88, 95% CI 0.62–1.25), two of the cohort studies enrolled incident cases of T2DM (pooled OR 1.27, 95% CI 1.15–1.40), and the remaining four cohort studies used a combination of methods to determine the T2DM (pooled OR 1.38, 95% CI 1.24–1.55; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…T2DM represents a continuum ranging from individuals who are unaware of their disease state, to those who are aware but do not comply with management and are uncontrolled, and those who are diet controlled, tablet controlled, or insulin controlled, These factors were not considered in our analyses, and future studies may use biomarkers of glycemic control to further study the effects of T2DM severity on PD 66 . For example, a recent study in non‐diabetic patients reported that midlife variability in glycemic control was associated with future PD 35 . Finally, our analysis does not consider that T2DM might influence markers of PD progression (motor and cognitive scores) independently of a direct effect on PD, and diabetic neuropathy and cognitive impairment due to small vessel disease are also commonly observed in older patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better explain this result, we conducted subgroup analysis and interaction test. According to whether the age is less than 65 years old or not, it can be divided into two parts: less than 65 years old and greater than or equal to 65 years old 27 , 28 . According to WHO standards, BMI is divided into four parts: < 18.5 kg/m 2 , 18.5 ~ 24.9 kg/m 2 , 25.0 ~ 29.9 kg/m 2 and ≥ 30.0 kg/m 2 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…In vivo and in vitro studies have also revealed a relationship between glucose fluctuation and endothelial cell/endothelium damage [ 14 16 ]. Furthermore, we reported that visit-to-visit variability of FPG may be a significant predictor of chronic cardiometabolic and neurodegenerative diseases, such as type 2 diabetes [ 17 ], cardiovascular disease [ 18 ], non-alcoholic fatty liver disease [ 19 ], and Parkinson’s disease [ 20 ] in the Korean general population without diabetes.…”
Section: Introductionmentioning
confidence: 99%